LRP-1-dependent control of calpain expression and activity: A new mechanism regulating thyroid carcinoma cell adhesion - Langlois, Benoit; Martin, Julie; Schneider, Christophe; Hachet, Cathy; Terryn, Christine; Rioult, Damien; Martiny, Laurent; Théret, Louis; Salesse, Stéphanie; Dedieu, Stéphane (Frontiers in Oncology, 2022)
The low-density lipoprotein receptor-related protein 1 (LRP1) is a multifunctional endocytic receptor mediating the clearance of various molecules from the extracellular matrix. LRP1 also regulates cell surface expression of matrix receptors by modulating both extracellular and intracellular signals, though current knowledge of the underlying mechanisms remains partial in the frame of cancer cells interaction with matricellular substrates. In this study we identified that LRP1 downregulates calpain activity and calpain 2 transcriptional expression in an invasive thyroid carcinoma cell model. LRP1-dependent alleviation of calpain activity limits cell-matrix attachment strength and contributes to FTC133 cells invasive abilities in a modified Boyden chamber assays. In addition, using enzymatic assays and co-immunoprecipitation experiments, we demonstrated that LRP1 exerts post-translational inhibition of calpain activity through PKA-dependent phosphorylation of calpain-2. This LRP-1 dual mode of control of calpain activity fine-tunes carcinoma cell spreading. We showed that LRP1-mediated calpain inhibition participates in talin-positive focal adhesions dissolution and limits β1-integrin expression at carcinoma cell surface. In conclusion, we identified an additional and innovative intracellular mechanism which demonstrates LRP-1 pro-motile action in thyroid cancer cells. LRP-1 ability to specifically control calpain-2 expression and activity highlights a novel facet of its de-adhesion receptor status.